Characteristics and Presentation of Women with Ectopic Pregnancy - Shazia Saqib, Sabeena Umer, Saadia Khanam, Asma Qamar Mudassir, Nosheen Bano, Sumera Nighat (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine characteristics and presentation of women with ectopic pregnancy (EP). Study Design: A cross-sectional study. Place and Duration of the Study: The Department of Obstetrics & Gynaecology, Sialkot Medical College, Sialkot Pakistan from January 2021 to December 2021. Material and Methods: A total of 39 women aged between 18 to 45 years and diagnosed with EP were included. Age, parity status, clinical presentation, diagnostic modality and sides affected were noted. A special proforma was designed to record all study data. For statistical analysis, SPSS version 26.0 was employed. Numeric data was shown as mean and standard deviation while categorical variables were represented as frequencies/percentages. Results: In a total of 39 women with ectopic pregnancy, mean age was 28.6±6.4 years while 23 (59.0%) women were aged between 18 to 30 years. There were 9 (23.1%) women who were nulliparous. Residential status of 22 (56.4%) women was rural in 22 (56.4%) patients. Condition of tube revealed ruptured EP among 37 (94.9%) women. Most common clinical presentation was abdominal/pelvic pain in 37 (94.9%) women while amenorrhea and vaginal bleeding were observed in 32 (82.1%) and 30 (76.9%) women respectively. Conclusion: Most commonly observed clinical presentation among women with ectopic pregnancy were abdominal/pelvic pain, amenorrhea and vaginal bleeding while almost half of the patients presented with shock. Keywords: Amenorrhea, abdominal pain, ectopic pregnancy, shock, vaginal bleeding.